ISOLATION OF POTENTIAL ANTIMICROBIAL METABOLITE FROM ENDOPHYTIC BACILLUS AMYLOLIQUEFACIENS DL06 OF CARNIVOROUS PLANT DROSERA BURMANNII VAHL. - CHAUDHURI, MADHUBANTI; AK, PAUL; PAL, ARUNDHATI (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: Exploitation of bacterial endophytes for production of antimicrobial substances has led to the discovery of novel natural metabolites of diverse chemical nature. The present study focuses attention toward optimization of cultural conditions for production of antimicrobial compound(s) by an endophytic bacterium DL06 followed by its extraction and partial purification. Methods: The leaf endophytic bacterium Bacillus amyloliquefaciens DL06 (GenBank Accession no. MK696415, Microbial Culture Collection Accession no. 4186) isolated from carnivorous plant Drosera burmannii has been identified as a potent producer of antimicrobial metabolite following agar cup assay against several test bacterial and fungal strains. Cultural conditions for production of antimicrobials were optimized by “one variable at a time” method. The active fraction was isolated and purified partially using solvent extraction, thin-layer chromatography, and high performance liquid chromatography (HPLC) analysis. Results: B. amyloliquefaciens DL06 produced maximum antimicrobial compound in tryptic soy broth and Davis–Mingioli’s medium when grown under shake culture. Production of the antimicrobial metabolite has been optimized for the inoculum density, aeration, temperature, pH as well as carbon, and nitrogen sources. The antimicrobial metabolite was extracted from the cell-free culture filtrate in butanol and partially purified by silica gel column chromatography and HPLC. Conclusions: The antimicrobial metabolite, tentatively identified as quercetin showed broad spectrum bioactivity affecting several fungi and a number of Gram-positive and Gram-negative bacteria.